From "Stone-Age" to "Real-Time" : exploring Papuan temporalities, mobilities and religiosities - Slama, Martin; Munro, Jenny (Monographs in anthropology series., 2015)
There are probably no other people on earth to whom the image of the 'stone-age' is so persistently attached than the inhabitants of the island of New Guinea, which is divided into independent Papua New Guinea and the western part of the island, known today as Papua and West Papua. From 'Stone-Age' to 'Real-Time' examines the forms of agency, frictions and anxieties the current moment generates in West Papua, where the persistent 'stone-age' image meets the practices and ideologies of the 'real-time' "a popular expression referring to immediate digital communication. The volume is thus essentially occupied with discourses of time and space and how they inform questions of hierarchy and possibilities for equality. Papuans are increasingly mobile, and seeking to rework inherited ideas, institutions and technologies, while also coming up against palpable limits on what can be imagined or achieved, secured or defended. This volume investigates some of these trajectories for the cultural logics and social or political structures that shape them. The chapters are highly ethnographic, based on in-depth research conducted in diverse spaces within and beyond Papua. These contributions explore topics ranging from hip hop to HIV/ AIDS to historicity, filling much-needed conceptual and ethnographic lacunae in the study of West Papua